O azul nos hábitos e nas batinas: o surgimento de uma congregação religiosa masculina e questão de gênero - Munhoz, Juliana Neri (2021)
The blue in the habits and the cassocks is about the appearance of the Blue Brothers, an unusual phenomenon in religious congregations, as a male religious group arises from a female one. We refer to the Congregation of the Sisters of the Immaculate Conception of Castres, the Blue Sisters, a Catholic Congregation of French origin, founded in 1836, which branched out and managed a male group in 2003: the Blue Brothers and their Public Association of Missionary Faithful of Our Lady Immaculate Conception of Castres, installed in Santa Cruz, Bolivia. They had their first formative experiences with the Blue Sisters and became priests in 2016. In this process, a new game of social relations and power in the Congregation is manifested. Our approach was based on the theoretical discussion of gender to be able to observe possible tensions and changes that occurred in the ecclesial structure due to this phenomenon. Thus, we guide this research based on the following questions: Why after so many years of existence of the Congregation of the Blue Sisters the blue brothers appear? How was this novelty seen by the blue sisters and how did gender relations work in this context? How were power relations configured within the Congregation, observing the gender issue? The work was carried out through a documental analysis of religious groups and empirical research, using the method of qualitative interviews and field observations. This debate brought new questions regarding the participation and performance of women in the Catholic Church